Sepsis and the muscle tissue. A narrative review - Oikonomou Eleousa; Paraskevas Themistoklis; Velissaris Dimitris (Sciendo, 2021)
Sepsis and septic shock are considered major factors in the development of myopathy in critically ill patients, which is correlated with increased morbidity rates and ICU length of stay. The underlying pathophysiology is complex, involving mitochondrial dysfunction, increased protein breakdown and muscle inexcitability. Sepsis induced myopathy is characterized by several electrophysiological and histopathological abnormalities of the muscle, also has clinical consequences such as flaccid weakness and failure to wean from ventilator. In order to reach definite diagnosis, clinical assessment, electrophysiological studies and muscle biopsy must be performed, which can be challenging in daily practice. Ultrasonography as a screening tool can be a promising alternative, especially in the ICU setting. Sepsis and mechanical ventilation have additive effects leading to diaphragm dysfunction thus complicating the patient's clinical course and recovery. Here, we summarize the effects of the septic syndrome on the muscle tissue based on the existing literature.